A robust, selective, and flexible RF front-end for wideband sampling receivers - Itamar Melamed; Sivan Toledo (ICT Express, 2017)
In this paper, we describe the design and evaluation of a second-generation front-end unit for wideband sampling radio receivers. The unit contains a surface acoustic wave (SAW) filter to protect the receiver from strong out-of-band signals, an RF limiter to protect both the filter and the receiver from physical damage due to strong signals, and a bias tee with a DC limiter to provide DC power to a masthead low-noise amplifier, if one is used. The unit allows receivers such as those of the universal software radio peripheral (USRP) N-series type to be effectively used in RF environments with weak signals and strong in-band and out-of-band interferences.